Human Serum Albumin Cys34 Adducts in Newborn Dried Blood Spots: Associations With Air Pollution Exposure During Pregnancy - Funk, William E.; Montgomery, Nathan; Bae, Yeunook; Chen, Jiexi; Chow, Ting; Martinez, Mayra P.; Lurmann, Fred; Eckel, Sandrah P.; McConnell, Rob; Xiang, Anny H. (Frontiers in Public Health, 2021)
Background: Increasing evidence suggests that exposure to air pollution during pregnancy is associated with adverse pregnancy outcomes. However, biomarkers associated with air pollution exposure are widely lacking. Objectives: We investigated relationships between air pollution exposure during pregnancy and human serum albumin Cys34 (HSA-Cys34) adducts in newborn dried blood spots (DBS) samples. Methods: Newborn DBS were obtained from a state archive for 120 children born at one Kaiser Permanente Southern California (KPSC) hospital in 2007. These children were selected based on estimated residential air pollution exposure during pregnancy to PM2.5, PM10, NO2, O3. HSA-Cys34 adducts, selected based on previously reported relationships with air pollution exposure and oxidative stress, were measured. Results: Six adducts measured in newborn DBS samples were associated with air pollution exposures during pregnancy; these included direct oxidation products, adducts formed with small thiol compounds, and adducts formed with reactive aldehydes. Two general trends were identified: Exposure to air pollution late in pregnancy (i.e., in the last 30 days) was associated with increased oxidative stress, and exposure to air pollution earlier in pregnancy (i.e., not in the last 30 days) was associated with decreased oxidative stress around the time of birth. Discussion: Air pollution exposure occurring during pregnancy can alter biology and leave measurable impacts on the developing infant captured in the newborn DBS adductome, which represents a promising tool for use in population studies.